1978
DOI: 10.1126/science.200.4341.561
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Abortion in T Cytoplasmic Male-Sterile Corn ( Zea mays ): A Suggested Mechanism

Abstract: A rapid replication of mitochondria (20- to 40-fold increase) occurs between the precallose and tetrad stages in the tapetum of N and T corn (Zea mays) anthers, followed by mitochondrial, tapetal, and pollen breakdown in T anthers. It is suggested that the altered DNA in T mitochondria may malfunction under these stress conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0
1

Year Published

1979
1979
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(64 citation statements)
references
References 18 publications
5
58
0
1
Order By: Relevance
“…A 20-to 40-fold increase in mitochondrion number has been found in some anther cells in maize (Warmke and Lee, 1978). The increased expression of several mitochondrial genes in maize microspores was proposed to result from a gene dosage effect caused by either the amplification of specific mitochondrial genes or an increase in mitochondrion number (MonBger et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 20-to 40-fold increase in mitochondrion number has been found in some anther cells in maize (Warmke and Lee, 1978). The increased expression of several mitochondrial genes in maize microspores was proposed to result from a gene dosage effect caused by either the amplification of specific mitochondrial genes or an increase in mitochondrion number (MonBger et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Together, these results indicated that the mitochondrial RlSP gene family is constitutively expressed at a basal level in tobacco plants and that the expression is also differentially regulated in an organ-or tissue-specific manner. The plant mitochondrion is functionally more versatile than animal mitochondria (Dennis, Microsporogenesis is a high-energy-demanding process that may impose stress on anther development (Warmke and Lee, 1978). Because microspores are nonphotosynthetic and contain only undifferentiated plastids and amyloplasts, energy in the form of ATP required for pollen development must be supplied mainly by mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of wild-type mitochondrial proteins and mitochondrial transcripts varies between different tissues in the plant (Conley and Hanson, 1994;Moneger et al, 1994), so aberrant proteins could possibly change in concentration during anther development. However, it is technically difficult to distinguish whether the concentration of a protein within a mitochondrion has changed in young anthers or whether apparently enhanced levels of a mitochondrial protein are an indirect result of an increase in mitochondrial number, which has been documented in the tapetum and wild-type sporogenous tissue of maize (Warmke and Lee, 1978). Perhaps the leading hypothesis for most types of CMS is that mitochondria have a special role to play in the tapetum, male meiotic cells, and/or developing microspores.…”
Section: A Special Role For Mitochondria In Pollen Development?mentioning
confidence: 99%
“…However, as is the case with rice COX11 and other CMS systems, the mode of action may affect more than one category. An additional interesting dimension is that while the expression of CMS genes does not appear to be restricted to the male reproductive tissues in many species (Warmke and Lee, 1978;Abad et al, 1995;Yamamoto et al, 2008;Chen and Liu, 2014), accumulation of CMS-related proteins can be highly spatiotemporally specific to induce CMS (Abad et al, 1995;Wang et al, 2006;Luo et al, 2013).…”
Section: And [4]mentioning
confidence: 99%